The curtain went up, my pants fell down - Winkler, Henry, 1945- (Hank Zipzer, the world's greatest underachiever, 2007)
Failing fifth grade math, Hank must depend on Heather, the class brain, to help him get a "B" on the next test in order for him to be eligible to play the lead in the school play, "The King and I."